EVALUATION OF THE PERCEPTION TOWARDS RESEARCH INVOLVING HUMAN BEINGS IN BRASILEAN POST DEGREE STUDENTS - Garbin, Clea Adas Saliba [UNESP] (2007)
In Brazil, research involving human beings must obey to ethical norms foresaw by the 196/96 National Health Council Resolution of the Ministry of Health. This paper gives account of a knowledge evaluation about some concepts and rules established by the resolution by Dental post degree students. It is concluded that in spite of the spreading and importance of the resolution most students do not know about it. In the same situation are those who work in research.